2022
DOI: 10.1111/ped.14937
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the coronavirus disease 2019 pandemic on pediatric hospitalization in Kitami, Japan

Abstract: Background Coronavirus disease 2019 (COVID‐19) has drastically changed the recommended activities and environment for patients worldwide. Our aim was to assess the impact of COVID‐19 on pediatric hospitalizations in Kitami, Japan. Methods A retrospective, single‐center study was conducted on hospitalized patients aged 0–14 years at the Japanese Red Cross Kitami Hospital. We compared the incidence of pediatric patients hospitalized in 2020 with those in 2017–2019. Results The number of pediatric hospitalized pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…18 Although our study did not show an increase in the absolute number of foreign body presentations, other studies performed in Italy, Britain and Japan have shown an increase throughout the COVID-19 pandemic, primarily with magnet and button battery ingestions as well as with overall hospitalization. [18][19][20] Furthermore, our study demonstrated that foreign body ingestions remain a common presenting complaint even throughout a pandemic and EDs should be equipped to manage them.…”
Section: Discussionmentioning
confidence: 71%
“…18 Although our study did not show an increase in the absolute number of foreign body presentations, other studies performed in Italy, Britain and Japan have shown an increase throughout the COVID-19 pandemic, primarily with magnet and button battery ingestions as well as with overall hospitalization. [18][19][20] Furthermore, our study demonstrated that foreign body ingestions remain a common presenting complaint even throughout a pandemic and EDs should be equipped to manage them.…”
Section: Discussionmentioning
confidence: 71%
“…Regardless of the continent in which the study was performed, most reports agreed on a decreased occurrence of RSV pediatric hospitalization during the COVID-19 pandemic period compared to previous seasons [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 24 ]. Later, many countries experienced delayed RSV peaks, leading to unseasonal outbreaks and hospitalizations [ 7 , 8 , 9 , 10 , 13 , 14 , 15 , 16 , 19 , 20 , 21 , 22 , 23 ]. Of note, among inpatients, RSV disease has been described as more severe than in the past and may have more frequently required oxygen supplementation or intensive care assistance [ 7 , 8 , 9 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 95%
“…In conclusion, 18 records were included in the revision [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The included studies analyze RSV pediatric hospitalization in COVID-19 era in Asia [ 5 ], America [ 2 ], Europe [ 7 ], and Oceania [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations